Role of Chaos in spread spectrum communication: A Brief Survey - Divya Singh, AasheeshShukla (International Journal of Advanced Science and Technology, 2020)
Due to the spreading nature of chaos, chaos based spread spectrum (CBSS) communication has become anfascinatingpart of research in the field of communication. Many research papers have been devoted to chaos based SS communication and mainly on synchronization issue. Based on the exploration; chaos theory is studied in this paper and then chaos based SS system are discussed with different maps. Role of chaos based spectrum is discussed for different system, which is pretty new and favourablepractice in this field. Issues related to synchronization have also been addressed, along with applications, challenges and open research issues.